Prenatal diagnosis of a homozygous variant of SUMF1 in a fetus with hydrops fetalis using chorionic villus sampling - Nguyen, Thi Sim; Nguyen, Duc Anh; Mai, Trong Hung; Ho, Khanh Dung; Vuong, Thi Bich Thuy; Luong, Thi Lan Anh; Nguyen, Thi Minh Ngoc; Tran, Duc Phan; Tran, Thi Kiem; Nguyen, Ngoc Dung (Vietnam Journal of Biotechnology, 2026)
Nonimmune hydrops fetalis (NIHF) is a severe prenatal condition with a broad etiological spectrum, including chromosomal abnormalities, structural malformations, congenital infections, and inherited metabolic disorders. Early identification of the underlying cause is essential for accurate prognosis, clinical decision-making, and genetic counseling. Here, we report the prenatal diagnosis of a fetus presenting with early-onset NIHF caused by a homozygous missense variant in the SUMF1 gene, detected through first-trimester chorionic villus sampling (CVS). A 27-year-old gravida 5 woman with a history of two previous pregnancies affected by unexplained hydrops fetalis was referred at 12 weeks and 3 days of gestation. Ultrasound examination revealed markedly increased nuchal translucency, generalized hydrops fetalis, and absence of the nasal bone. Given the recurrent phenotype and early gestational presentation, invasive prenatal diagnosis was performed using CVS. Clinical exome sequencing identified a homozygous SUMF1 variant (NM_182760.4: c.538T>A, p.Trp180Arg), which is absent from population databases and has been reported only once in ClinVar as a variant of uncertain significance. Subsequent Sanger sequencing confirmed heterozygous carrier status in both parents and the unaffected sibling, consistent with autosomal recessive inheritance. SUMF1 encodes the sulfatase-modifying factor 1, a critical enzyme required for post-translational activation of all sulfatases. Biallelic pathogenic variants in SUMF1 cause multiple sulfatase deficiency, an ultra-rare lysosomal storage disorder that may present prenatally with hydrops fetalis. The severe and recurrent fetal phenotype observed in this family strongly supports the pathogenic relevance of the identified variant. This case highlights the diagnostic value of early invasive prenatal testing, particularly CVS combined with next-generation sequencing, in pregnancies complicated by early-onset or recurrent NIHF. Early molecular diagnosis enables timely counseling, informed reproductive decision-making, and appropriate planning for future pregnancies.